Isolation and Evaluation of Antinociceptive Activity of Sulfur-Containing Iridoid Glucosides from Paederia scandens - Jin, Di; Li, Zhixiong; Chen, Mingcang; Fan, Mingsong; Sun, Zhaolin; Jiang, Weixin; Wu, Bin; Huang, Chenggang (Asian Journal of Chemistry, 2011)
Isolate and purify the sulfur-containing iridoid glucosides from Paederia scandens. Three sulfurcontaining iridoid glucosides (1-3) were isolated and the structures of them were elucidated as paederosides (1), paederosidic acid (2) and paederosidic acid methyl ester (3) by spectroscopic analysis. The sulfur-containing iridoid glucosides were evaluated on antinociceptive activity in mice using thermal models of nociception. Both paederosidic acid (2, 120 mg/kg, i.g. or 70 mg/ kg, i.p.) and paederosidic acid methyl ester (3, 70 mg/kg, i.p.) produced significant inhibitory activity on thermal nociception in the hot plate test. Paederoside (1, 70 mg/kg, i.p.) had not produced significant antinociceptive effects in the hot plate test.